23.7k views
5 votes
What is the average rate of change
y - 3 = -12 (x + 4)​​

User Lyra
by
5.6k points

2 Answers

5 votes

Answer:


-(3)/(10)

Explanation:

The average rate of change of a function f ( x ) over the interval [ a , b ] is


=(f(b)-f(a))/(b-a)


f(x)=(3)/(x-2)

and
[a,b]=[4,7]


f(b)=f(7)=(3)/(7-2)=(3)/(5)


f(b)=f(4)=(3)/(4-2)=(3)/(2)

The rate of change is


=(f(b)-f(a))/(b-a)


=((3)/(3) -(3)/(2) )/(7-4)


=-(9)/(10) *(1)/(3) =-(3)/(10)

User Eugene Talagrand
by
5.7k points
2 votes

Answer:


- 12x

Explanation:


y - 3 = - 12(x + 4) \\ y - 3 = - 12x - 48 \\ y = - 12x - 45

Thr answer is the slope.

User Balbino
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.